Optimizing CV Matching with Job Vacancies Using the Boyer-Moore Algorithm - Surbakti, Eunike Endariahna (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2025)
According to a survey conducted by a public survey agency, there was a decline in percentage from 37% to 20%, indicating a gap still exists between skills required by the job market and those possessed by job seekers. To address this issue, this study aims to assess the alignment between data from curriculum vitae (CV) and job vacancies. Boyer-Moore algorithm is implemented through a web-based system. System extracts text from a PDF file, which is used in the application of Boyer-Moore algorithm. System also retrieves selected job vacancy data and generates keywords using YAKE (Yet Another Keyword Extractor). Before processing with Boyer-Moore algorithm, all data undergoes pre-processing. Algorithm's output is either a